Pemanfaatan Daun Kersen (Muntingia calabura L.) dalam Penanganan Diabetes Mellitus - Dede Christian Kurnia (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2020)
Diabetes mellitus (DM) or better known as diabetes, is one of the diseases caused by high blood sugar accompanied by disorders of carbohydrate, fat, and protein metabolism as a result of insufficient insulin function. a study by Hendra Stevani, et al in 2016 concerning the effectiveness of the Decoction of Kersen Leaves (Muntingia calabura L.) on Reducing Blood Glucose Levels in Mice (Mus musculus). Cherry leaves are proven to reduce blood sugar levels conducted in animal experiments in the form of mice, with a concentration of 15%